# 5x+3(-3x+2)=4x+9

## Simple and best practice solution for 5x+3(-3x+2)=4x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 5x+3(-3x+2)=4x+9 equation:

Simplifying
5x + 3(-3x + 2) = 4x + 9
Reorder the terms:
5x + 3(2 + -3x) = 4x + 9
5x + (2 * 3 + -3x * 3) = 4x + 9
5x + (6 + -9x) = 4x + 9
Reorder the terms:
6 + 5x + -9x = 4x + 9
Combine like terms: 5x + -9x = -4x
6 + -4x = 4x + 9
Reorder the terms:
6 + -4x = 9 + 4x
Solving
6 + -4x = 9 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
6 + -4x + -4x = 9 + 4x + -4x
Combine like terms: -4x + -4x = -8x
6 + -8x = 9 + 4x + -4x
Combine like terms: 4x + -4x = 0
6 + -8x = 9 + 0
6 + -8x = 9
Add '-6' to each side of the equation.
6 + -6 + -8x = 9 + -6
Combine like terms: 6 + -6 = 0
0 + -8x = 9 + -6
-8x = 9 + -6
Combine like terms: 9 + -6 = 3
-8x = 3
Divide each side by '-8'.
x = -0.375
Simplifying
x = -0.375`